Network of scientific publications in information science - Pečarić, Đilda (2011)
Bibliometric methods (bibliographic coupling and co-citation) implicitly postulate impact factor and influence factor as criteria for evaluation of „knowledge maps“ or „intellectual structures“. However, bibliometric methods can also be used for presentations of „Historio-Bibliography“, that is genealogical tree of primordial publications. Visual presentation of history of key publications which E. Garfield (2001) named historiograph. Using corpus of bibliographic data from doctoral dissertations (1978-2009) we want to show the network of nodal publications from information science in the period from 1960 until today. Historiographs for presentations of Network of scientific publications could be generated with different methods (N. P. Hummon, P. Doreian, 1989): critical path method, bibliographic coupling method, citation method, co-citation method. We use these methods in order to show, by historiograph, historical overview of key publications in information science in Croatia. Chronological presentation of the development of scientific publication network also enables chronological analysis of certain authors’ roles in scientific community from researchers and scholars to predecessors.
Projekt MZOS
ENG